Composite negative electrode and lithium ion battery using same

By forming a SEI film with a thickness of 10 to 25 nm, rich in LiF and fluorine element content on the negative electrode surface of the lithium-ion battery, combined with the method of introducing elements such as carbon, oxygen, and phosphorus, the problems of self-discharge and low calendar life of lithium-ion batteries are solved, and the capacity stability and safety of the battery are significantly improved.

CN119673959APending Publication Date: 2025-03-21EVE ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411282155.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Lithium-ion batteries have problems such as large self-discharge and low calendar life. The sparse porous structure of conventional SEI films cannot effectively block the decomposition of the electrolyte, resulting in a decrease in battery capacity and frequent side reactions.

Method used

A composite negative electrode is provided, and a solid electrolyte interface film (SEI film) with a thickness of 10 to 25 nm, rich in LiF and fluorine element content is 15 to 40% is formed on the surface of the negative electrode to resist the rupture of the SEI film caused by the expansion of the negative electrode during lithium embedding/delithation, and enhance the density and mechanical strength of the SEI film by introducing elements such as carbon, oxygen, and phosphorus.

Benefits of technology

Effectively alleviate the self-discharge problem of lithium-ion batteries, improve the battery capacity stability, extend the calendar life and cycle life, and improve the battery safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043679710000051
    Figure BDA0005043679710000051
  • Figure BDA0005043679710000061
    Figure BDA0005043679710000061
  • Figure BDA0005043679710000062
    Figure BDA0005043679710000062
Patent Text Reader

Abstract

The invention provides a composite negative electrode and a lithium ion battery using the same, the composite negative electrode comprises a negative electrode and a solid electrolyte interface film arranged on the surface of the negative electrode, and the thickness of the solid electrolyte interface film is 10-25nm; the solid electrolyte interface film comprises lithium fluoride, and the content of fluorine in the solid electrolyte interface film is 15-40%. According to the composite negative electrode provided by the invention, a layer of SEI film which is rich in LiF and has the thickness of 10-25nm is formed on the surface of the negative electrode, so that SEI film breakage caused by negative electrode expansion in a lithium intercalation / lithium removal process can be resisted, the self-discharge problem of the lithium ion battery can be relieved, and the calendar life, the cycle life, the safety and other performances of the lithium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a composite negative electrode and a lithium ion battery using the composite negative electrode. Background Art

[0002] As of 2024, the lithium-ion battery industry has maintained a rapid growth trend worldwide. As a major producer of lithium-ion batteries, China's output and market share continue to rise. In 2023, China's total lithium-ion battery output exceeded 940GWh, a year-on-year increase of 25%, and the industry's total output value exceeded 1.4 trillion yuan. In the same year, China's total lithium battery exports reached 457.4 billion yuan, a year-on-year increase of more than 33%. It can be seen that China's lithium-ion battery industry is in a period of rapid development. With the growth of demand in new energy vehicles, energy storage systems, and portable electronic devices, the scale of the lithium-ion battery market continues to expand. Therefore, in order to occupy the scale of the lithium-ion battery market, companies need to continue to invest in research and development to improve existing technologies and develop new battery materials, manufacturing processes and designs to improve the electrochemical performance of batteries.

[0003] In the current electric vehicle and energy storage fields, the lithium-ion batteries provided still have the problems of large self-discharge and low calendar life. Among them, a stable solid electrolyte interface film (SEI film) is the basis for the normal operation of lithium-ion batteries and affects the battery's calendar life, cycle life and safety.

[0004] The conventional SEI film is formed during the first week of charge and discharge of the lithium-ion battery. During the first charge, as the negative electrode potential continues to decrease, the electrolyte is reduced, decomposed and deposited on the negative electrode surface, thereby forming an SEI film. However, the conventional SEI film of lithium-ion batteries is affected by the film formation mechanism. Due to the high organic content of the conventional SEI film, the conventional SEI film appears sparse and porous. Therefore, the sparse and porous SEI film cannot prevent the continuous decomposition of the electrolyte on the negative electrode surface in subsequent cycles. This will cause the battery capacity to continue to decrease and the side reactions to continue, which is particularly significant at high temperatures. Therefore, researchers have conducted research on SEI membranes. The main method is to synthesize membranes of different compositions and structures on the negative electrode surface, but these SEI membranes still cannot improve the problem of self-discharge in lithium-ion batteries, and the SEI membranes provided by the current existing technology have complex synthesis conditions and are difficult to apply industrially. Summary of the invention

[0005] In order to improve the self-discharge problem of lithium-ion batteries and increase the calendar life of lithium-ion batteries, the present invention provides a composite negative electrode and a lithium-ion battery using the composite negative electrode.

[0006] According to one aspect of the present invention, a composite negative electrode is provided, which includes a negative electrode and a solid electrolyte interface film (SEI film) arranged on the surface of the negative electrode, the thickness of the solid electrolyte interface film is 10-25nm; lithium fluoride is included in the solid electrolyte interface film, and the content of fluorine in the solid electrolyte interface film is 15-40%. The composite negative electrode provided by the present invention can resist the rupture of the SEI film caused by the expansion of the negative electrode during the lithium insertion / de-lithiation process by forming a layer of LiF-rich SEI film with a thickness of 10-25nm on the surface of the negative electrode, thereby alleviating the problem of self-discharge of lithium-ion batteries. At the same time, the present invention can be known through X-ray photoelectron spectroscopy (XPS) test that when the content of fluorine in the SEI film on the surface of the negative electrode is 15-40%, the SEI film can be made denser, thereby reducing the direct contact between the electrolyte and the lithium-rich graphite negative electrode, reducing the possibility of side reactions between the negative electrode and the electrolyte, thereby improving the capacity stability of the battery, and thereby improving the calendar life, cycle life and safety of the lithium-ion battery.

[0007] Preferably, the content of lithium in the solid electrolyte interface film is 10-20%.

[0008] Preferably, the solid electrolyte interface film also includes carbon, and the content of carbon is 10-20%. The SEI film also includes carbon, indicating that the SEI film also includes organic matter, and the appropriate content of organic matter helps the SEI film to improve the lithium ion conductivity, enhance mechanical stability, and reduce stress caused by volume expansion or contraction; it can also improve compatibility and processability, and improve the compatibility between the SEI film and the electrode material.

[0009] Preferably, the solid electrolyte interface film also includes at least one of oxygen, phosphorus, boron, sulfur and nitrogen. Furthermore, by introducing at least one of oxygen, phosphorus, boron, sulfur and nitrogen into the solid electrolyte interface film, the mechanical strength of the SEI film can be enhanced, thereby further improving the stability of the SEI film, thereby giving the battery good cycle performance. When oxygen is introduced, it helps to improve the thermal stability of the SEI, and the oxygen-containing product has a higher decomposition starting temperature; it reduces the volume of the SEI film, forming a thinner SEI film, which is beneficial to cycle stability.

[0010] When phosphorus is introduced, it helps to promote the formation of fast ion diffusion channels in the SEI film, such as by forming LiF / Li3P grain boundaries with low lithium ion diffusion barriers, which can accelerate the transmission of lithium ions inside the SEI film, reduce the formation of lithium dendrites, and improve the cycle stability and fast charging capability of the battery. In addition, the introduction of phosphorus can also improve the mechanical properties and electrochemical activity of the SEI film, thereby improving the overall performance and safety of lithium metal batteries. Boron can effectively protect the lithium negative electrode and improve the performance and stability of the battery. This protective film has good uniformity and protective effect, can alleviate the growth of lithium dendrites, and can also effectively block the corrosion of lithium by moisture, oxygen or electrolyte, thereby improving the overall performance of the battery. Sulfur can effectively improve the protection ability of lithium and can guide the uniform deposition of lithium while maintaining a low active surface area, thereby preventing the reduction of the electrolyte. Nitrogen can promote the construction of a suitable solid electrolyte interface (SEI) layer on the electrode surface by adjusting the composition of the electrolyte.

[0011] Preferably, in the solid electrolyte interface film, the content of oxygen element is 10-20%; and / or, the content of phosphorus element is 2-10%; and / or, the content of boron element is 1-5%; and / or, the content of sulfur element is 1-5%; and / or, the content of nitrogen element is 1-5%.

[0012] Preferably, the negative electrode includes a negative electrode active material, and the negative electrode active material includes at least one of natural graphite, artificial graphite, hard carbon, soft carbon, graphene, and silicon-carbon material.

[0013] Preferably, the method for preparing a composite negative electrode comprises the following steps: S1. connecting the negative electrode to the positive electrode of the power source, and connecting the metallic lithium to the negative electrode of the power source; S2. subsequently adding a film-forming solution, and performing a lithium insertion reaction at a current range of 0.1 to 10A, with a reaction time of 10 to 600 seconds, to obtain a composite negative electrode. The present invention assembles an electrolytic cell with the negative electrode and metallic lithium (with the negative electrode as the working electrode and the metallic lithium as the counter electrode, which is equivalent to forming a button battery), and after connecting an external circuit, a lithium insertion reaction can occur at the negative electrode, and the current and voltage of the lithium insertion reaction can be regulated by controlling the external circuit. As the lithium insertion reaction proceeds, the potential of the negative electrode gradually decreases. When it is lower than the reduction decomposition potential of the lithium salt, the lithium salt can be reduced and decomposed on the surface of the negative electrode to form an SEI film. Therefore, the present invention can regulate the elemental composition and structure of the SEI film formed by regulating the current and time of the reaction.

[0014] Preferably, the membrane-forming solvent includes a solute, and the solute includes at least one of lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), and lithium trifluoromethanesulfonate (LiSO3CF3).

[0015] Preferably, the concentration of the solute in the membrane-forming solvent is 0.01 to 10 mol / L.

[0016] Preferably, the membrane-forming solvent includes a solvent, and the solvent includes at least one of tetrahydrofuran, dioxolane, ethylene glycol dimethyl ether, 2-methyltetrahydrofuran, hexyl oxide, and isopropyl ether.

[0017] The present invention can not only provide inorganic components such as LiF for the SEI film by regulating the components in the film-forming solvent, but also introduce at least one of carbon, oxygen and phosphorus elements into the SEI film, thereby further improving the stability of the SEI film, thereby improving the self-discharge problem of the lithium-ion battery and improving the calendar life, cycle life and safety of the lithium-ion battery.

[0018] Preferably, after S2, S3 is further included to wash and dry the obtained composite negative electrode.

[0019] Preferably, in S3, the cleaning treatment is cleaning the composite negative electrode by using ethylene glycol dimethyl ether.

[0020] Preferably, in S3, the drying treatment is to vacuum dry the composite negative electrode at 40 to 100°C for 1 to 6 hours.

[0021] A second aspect of the present invention is a lithium ion battery, comprising the composite negative electrode as described above.

[0022] Preferably, the lithium-ion battery comprises a positive electrode, the positive electrode comprises a positive electrode active material, and the positive electrode active material comprises at least one of lithium iron phosphate, a ternary material, and lithium cobalt oxide.

[0023] Preferably, the positive electrode active material is lithium iron phosphate. By using the composite negative electrode provided by the present invention, the self-discharge and low calendar life (storage performance) problems of lithium ion batteries using lithium iron phosphate as positive electrode materials can be significantly improved. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0025] Example 1

[0026] The method for preparing the composite negative electrode in this embodiment is as follows:

[0027] S1. Connect the negative electrode (with natural graphite as the negative electrode active material) to the positive electrode of the power source, and connect the metallic lithium to the negative electrode of the power source;

[0028] S2. Then, a film-forming solution was added, and a lithium insertion reaction was performed at a current range of 5A for 300 seconds to obtain a composite negative electrode;

[0029] S3. After the composite negative electrode was cleaned with ethylene glycol dimethyl ether, it was vacuum dried at 70° C. for 4 hours.

[0030] In this embodiment, a lithium-ion battery is prepared by the following method: the positive electrode material (lithium iron phosphate) is mixed with the conductive agent acetylene black and the binder PVDF in a mass ratio of 9:0.2:0.8, and a certain amount of organic solvent NMP is added, and the mixture is coated on an aluminum foil after stirring to form a positive electrode sheet. The negative electrode sheet adopts the composite negative electrode prepared above, and the diaphragm adopts Celgard2400 polypropylene porous membrane; the electrolyte uses a solution composed of EC, DMC and EMC in a mass ratio of 1:1:1 as the solvent of the electrolyte, and LiPF6 as the solute of the electrolyte, wherein the concentration of LiPF6 is 1.0 mol / L. The above-mentioned positive electrode sheet, negative electrode sheet, diaphragm and electrolyte are assembled into a lithium-ion battery in a glove box.

[0031] In each treatment group and each comparison group of this embodiment, the fluorine content and lithium content in the SEI film are used as variables to set different treatment groups and comparison groups, and the specific variables are shown in Table 1. The increase or decrease of the variables is achieved by regulating the solute concentration in the film-forming solution, and the material composition of the film-forming solution is shown in Table 1. In addition to the above differences, the methods and formulas for preparing the composite negative electrode and lithium-ion battery in each treatment group and each comparison group of this embodiment are strictly consistent.

[0032] Table 1. Variables of each treatment group and control group in Example 1

[0033]

[0034] Test Example 1

[0035] 1. Test subjects

[0036] The composite negative electrodes and lithium ion batteries prepared in each treatment group and control group in Example 1 were used as test objects. In addition, in this test example, a control group was also provided, which was prepared by referring to the method and formula for preparing a lithium ion battery provided by treatment group 1A of Example 1, and the difference therefrom was that the control group used a negative electrode instead of a composite negative electrode to prepare a lithium ion battery (i.e., there was no SEI film in the lithium ion battery).

[0037] 2. Test Method

[0038] (1) Cycle performance: The battery was cycled for 1000 cycles at 1C at room temperature with a voltage range of 2.5-3.65 V, and the capacity retention after the cycles was compared.

[0039] (3) Calendar life: Charge the battery to 50% and 90% SOC, place it at room temperature for 60 days, and test the battery open circuit voltage and DC resistance changes every 5 days.

[0040] (4) Elemental composition of SEI film: X-ray photoelectron spectroscopy (XPS) was used to test the elemental composition of SEI film.

[0041] (5) SEI film thickness: The thickness was observed using a transmission electron microscope (TEM).

[0042] 3. Test results and analysis

[0043] In this test example, the effects of fluorine and lithium on the SEI film are mainly explored, and the test results of this test example are shown in Table 2. In addition to LiF, the SEI films prepared in each treatment group and the comparison group of this embodiment also form lithium alkyl derivatives and fluorocarbon compounds, so in addition to fluorine and lithium elements, there are also other elements in this test example.

[0044] In treatment groups 1A to 4A and comparison groups 1A to 2A, the main focus is on exploring the changes in the content of fluorine in the SEI film and the effects on the SEI film and the lithium-ion batteries using it. In treatment groups 1A to 4A and comparison groups 1A to 2A, it can be found that with the increase in the content of fluorine in the SEI film, the improved self-discharge phenomenon, cycle performance, and calendar life performance of the lithium-ion batteries using it show a trend of first increasing and then decreasing. This shows that when the fluorine content in the SEI film meets the range of 15 to 40%, it has better performance.

[0045] The above tests have confirmed that the SEI film on the surface of the negative electrode of Dangdang meets the requirement of 15-40% fluorine content, which can make the SEI film denser, thereby reducing the direct contact between the electrolyte and the lithium-rich graphite negative electrode, and reducing the possibility of side reactions between the negative electrode and the electrolyte, thereby improving the capacity stability of the battery, and further improving the calendar life, cycle life and safety of the lithium-ion battery.

[0046] Table 2. Test results of this test case

[0047]

[0048] Example 2

[0049] The treatment groups and comparison groups of this embodiment prepare composite negative electrodes and lithium-ion batteries with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A is that when preparing the composite negative electrodes, the materials used for the film-forming solvent in the treatment groups and comparison groups of this embodiment are used as variables, and the variables are shown in Table 3. In addition to the above differences, the operation steps for preparing the composite negative electrodes and lithium-ion batteries in the treatment groups and comparison groups of this embodiment are strictly consistent with those of treatment group 1A of Example 1.

[0050] Table 3. Variables of each treatment group and control group in Example 2

[0051]

[0052]

[0053] Treatment Group 4B

[0054] This treatment group prepares the composite negative electrode and lithium ion battery with reference to the formula and method provided by treatment group 1B of Example 2. The difference from treatment group 1B is that this treatment group uses silicon material as the negative electrode active material, and the solute composition in the film-forming solvent is lithium bistrifluoromethanesulfonyl imide, and the solution composition is tetrahydropyran. Except for the above differences, the operation steps of preparing the composite negative electrode and lithium ion battery in this treatment group are strictly consistent with those of treatment group 1B of Example 2.

[0055] Test Example 2

[0056] 1. Test subjects

[0057] The composite negative electrodes and lithium-ion batteries prepared in the treatment groups and the control group in Example 2 were used as test objects. Control group 1B referred to the lithium-ion battery prepared in the control group provided in Test Example 1; control group 2B referred to control group 1B, and the difference from control group 1B was that the negative electrode active material in control group 2B was silicon material.

[0058] 2. Test Method

[0059] This test example refers to the test method provided in Test Example 1.

[0060] 3. Test results and analysis

[0061] The test data of this test example are shown in Table 4. Through this test example, it can be found that in the SEI film, different element compositions will affect the performance of the SEI film, and then affect the electrochemical performance of the lithium-ion battery using it. By comparing groups 1B to 2B and the control group, it can be clearly found that when the SEI film does not contain fluorine elements, its self-discharge problem is very prominent. This is because the SEI film rich in LiF and with a thickness of 10 to 25 nm provided by the present invention can resist the rupture of the SEI film caused by the expansion of the negative electrode during the lithium insertion / de-lithiation process, and alleviate the problem of self-discharge of lithium-ion batteries.

[0062] By comparing the data in treatment groups 1B to 3B, it can be found that for the negative electrode with graphite or hard carbon material as the negative electrode active material, the film-forming solution uses at least one of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate as the solute, and is combined with 2-methyltetrahydrofuran as the solution, which can obtain a dense and LiF-rich SEI film, thereby reducing the battery self-discharge and significantly improving the battery calendar life. Further, the above data can confirm that when the carbon content in the SEI film is 10-20%; and / or, the oxygen content is 10-20%; and / or, the phosphorus content is 2-10%, the performance of the SEI film can be further enhanced, thereby improving the calendar life, cycle life and safety of the lithium-ion battery.

[0063] In addition, it can be seen from the treatment group 4B and the control group 2B that when the negative electrode active material is a silicon material or a silicon-carbon material, when lithium bis(trifluoromethanesulfonyl)imide is used as a solute and tetrahydropyran is used as a solution in the film-forming solution, the performance degradation caused by silicon expansion can be reduced.

[0064] Table 4. Test results of this test case

[0065]

[0066] Example 3

[0067] The treatment groups 1C to 5C of this embodiment prepare composite negative electrodes and lithium-ion batteries with reference to the formula and method provided by the treatment group 1A of Example 1. The difference from the treatment group 1A is that the treatment groups 1C to 5C of this embodiment use the current and reaction time of the lithium insertion reaction as variables when preparing the composite negative electrodes, and the variables are shown in Table 5. In addition to the above differences, the operation steps for preparing the composite negative electrodes and lithium-ion batteries of the treatment groups 1C to 5C of this embodiment are strictly consistent with those of the treatment group 1A of Example 1.

[0068] Table 5. Variables of each treatment group and control group in Example 3

[0069] Group Current range Reaction time Treatment Group 1C 0.5A 300 seconds Treatment Group 2C 0.1A 600 seconds Treatment Group 3C 5A 60 seconds Treatment Group 4C 1A 300 seconds Treatment Group 5C 3A 5 seconds

[0070] Treatment Group 6C

[0071] This treatment group prepares the composite negative electrode and lithium-ion battery with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A is that, when preparing the composite negative electrode, each treatment group and the comparative group of this example prepares the SEI film on the negative electrode surface by atomic layer deposition. Except for the above differences, the formula for preparing the composite negative electrode and the operating steps for preparing the lithium-ion battery of this example are strictly consistent with those of treatment group 1A of Example 1.

[0072] Test Example 3

[0073] 1. Test subjects

[0074] The composite negative electrodes and lithium-ion batteries prepared in the treatment groups and the comparison group in Example 3 were used as test objects.

[0075] 2. Test Method

[0076] This test example refers to the test method provided in Test Example 1.

[0077] 3. Test results and analysis

[0078] The test results of this test example are shown in Table 6. Among them, it can be found through treatment groups 1C to 5C that the current and reaction time of the lithium insertion reaction will affect the thickness and density of the SEI film. In treatment groups 4C to 5C, the prepared SEI film is too thick or too thin. When the SEI film is too thick, it will increase the internal resistance of the battery, resulting in a decrease in the lithium ion transmission efficiency and accelerate the aging of the battery; when the SEI film is too thin, it is difficult to block the reaction between the electrolyte and the negative electrode material to a limited extent, resulting in a decrease in the battery cycle stability.

[0079] In addition, in the prior art, conventional methods for preparing SEI films include chemical vapor deposition (CVD), atomic layer deposition (ALD), sputtering, spin coating, etc. By comparing the data of treatment group 6C, it can be found that when other methods for preparing SEI films are used, an overly dense SEI film will affect the transmission rate of lithium ions, thereby affecting the cycle performance and calendar life of lithium-ion batteries.

[0080] Table 6. Test results of this test case

[0081]

[0082]

[0083] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A composite negative electrode, characterized in that: The composite negative electrode comprises a negative electrode and a solid electrolyte interface film arranged on the surface of the negative electrode, the thickness of the solid electrolyte interface film is 10-25nm; the solid electrolyte interface film comprises lithium fluoride, and the content of fluorine element in the solid electrolyte interface film is 15-40%.

2. The composite negative electrode according to claim 1, characterized in that: The solid electrolyte interface film also includes carbon element, and the content of the carbon element is 10-20%.

3. The composite negative electrode according to claim 2, characterized in that: The solid electrolyte interface film further includes at least one of oxygen, phosphorus, boron, sulfur and nitrogen.

4. The composite negative electrode according to claim 3, characterized in that: In the solid electrolyte interface film, the content of the oxygen element is 10-20%; And / or, the phosphorus content is 2-10%; And / or, the content of boron is 1-5%; And / or, the content of sulfur element is 1-5%; And / or, the content of nitrogen is 1-5%.

5. The composite negative electrode according to claim 1, characterized in that: The negative electrode includes a negative electrode active material, and the negative electrode active material includes at least one of natural graphite, artificial graphite, hard carbon, soft carbon, graphene, and silicon-carbon material.

6. The composite negative electrode according to any one of claims 1 to 5, characterized in that: The method for preparing the composite negative electrode comprises the following steps: S1. connecting the negative electrode to the positive electrode of the power supply, and connecting the metallic lithium to the negative electrode of the power supply; S2. Then, a film-forming solution is added to carry out a lithium insertion reaction at a current range of 0.1 to 10 A. The time of the lithium insertion reaction is 10 to 600 seconds to obtain the composite negative electrode.

7. The composite negative electrode according to claim 6, characterized in that: The membrane-forming solvent includes a solute, and the solute includes at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium hexafluoroarsenate, and lithium trifluoromethanesulfonate.

8. The composite negative electrode according to claim 6, characterized in that: The membrane-forming solvent includes a solvent, and the solvent includes at least one of tetrahydrofuran, dioxolane, ethylene glycol dimethyl ether, 2-methyltetrahydrofuran, hexene oxide, tetrahydropyran, and isopropyl ether.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite negative electrode according to any one of claims 1 to 8.

10. The lithium ion battery according to claim 9, characterized in that: The lithium-ion battery comprises a positive electrode, and the positive electrode comprises a positive electrode active material; wherein the positive electrode active material comprises at least one of lithium iron phosphate, a ternary material, and lithium cobalt oxide.

Citation Information

Patent Citations

  • Lithium ion battery and lithium ion battery pack

    CN112909335A

  • Pre-lithiated silicon-based negative electrode material as well as preparation method and application thereof

    CN113871605A

  • Secondary battery and device

    CN116314595A

  • Pre-lithiation negative electrode material, preparation method thereof, pre-lithiation electrochemical device and application

    CN116487574A